2021
DOI: 10.3390/ijerph18020626
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of a Positive Parenting Experience in Prison

Abstract: The two goals of this study were: (1) to explore the relationship of a parent’s experience in prison in combination with a range of characteristics relating to the parent in prison, to the children, and to the caregiver, and (2) to explore the role of sex and nationality in this relationship. A total of 202 parents in prison (99 men and 103 women; 106 Spanish and 96 foreigners) participated in this study. To maximize the understanding of the questions, in-person interviews were conducted to collect answers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Moreover, it has been observed that the caregiver’s health, as well as the relationship between the caregiver and the child, is crucial in the impact on the well-being and development of the child, especially in middle childhood and adolescence. For this reason, programs should not only be oriented towards working with minors but also with the caregiver figure, focusing on enhancing their well-being and creating a good relationship between the caregiver and the minor [ 88 ]. In this sense, an appropriate intervention could be systemic family therapy, since much importance is given to the minor’s interpersonal relationships with different agents who influence their development (mainly the primary caregiver and the parent in prison).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been observed that the caregiver’s health, as well as the relationship between the caregiver and the child, is crucial in the impact on the well-being and development of the child, especially in middle childhood and adolescence. For this reason, programs should not only be oriented towards working with minors but also with the caregiver figure, focusing on enhancing their well-being and creating a good relationship between the caregiver and the minor [ 88 ]. In this sense, an appropriate intervention could be systemic family therapy, since much importance is given to the minor’s interpersonal relationships with different agents who influence their development (mainly the primary caregiver and the parent in prison).…”
Section: Discussionmentioning
confidence: 99%